Penicillium expansum Link strain for a biometallurgical method to recover REEs from WEEE. (February 2017) - Di Piazza, Simone; Cecchi, Grazia; Cardinale, Anna Maria; Carbone, Cristina; Mariotti, Mauro Giorgio; Giovine, Marco; Zotti, Mirca
Highlights: A three weeks biometallurgical method to recover REEs using fungi was set up. The strain exploited can bioconcentre REEs from WEEE up to 3000 times, in its biomass. This low-cost process allows the production of a concentrated REE ions acid solution. Abstract: Due to the wide range of applications in high-tech solutions, Rare Earth Elements (REEs) have become object of great interest. In the last years several studies regarding technologies for REE extraction from secondary resources have been carried out. In particular biotechnologies, which use tolerant and accumulator microorganisms to recover and recycle precious metals, are replacing traditional methods. This paper describes an original biometallurgical method to recover REEs from waste electrical and electronic equipment (WEEE) by using a strain of Penicillium expansum Link isolated from an ecotoxic metal contaminated site. The resulting product is a high concentrated solution of Lanthanum (up to 390 ppm) and Terbium (up to 1520 ppm) obtained from WEEE. Under this perspective, the proposed protocol can be considered a method of recycling exploiting biometallurgy. Finally, the process is the subject of the Italian patent application n. 102015000041404 submitted by the University of Genoa.